EFFECT OF ACIDULATED ROCK PHOSPHATE LEVELS ON AVAILABILITY OF PHOSPHORUS AND COPPER IN SOIL AND GROWTH OF MAIZE - & Al-Robiaee, Al-Janabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A wooden house pots experiment was carried out at College of Agriculture/ University of Baghdad using calcareous soil silty clay loam texture collected from one of farm fields in Al-Jadriya region/ Baghdad governorate to study the effect of acidulated phosphate rock levels in availability of phosphorus and copper and growth of maize (Zea mays L.) and phosphorus, copper contents. Corn seeds (Zea mays L.) 5018 (produced office of agricultural research/ ministry of agriculture) were sows in Aug. 2014 with Six seeds in each pot then five plant were removed after one week from the growth. Completely Randomized Block Design (CRD) was used and three levels of partial acidulated phosphate rock 40% (0, 40 and 80 Kg p ha-1) as resource of phosphorus. The result of the research showed phosphorus availability in soil were increased by 104.00% compared with control treatment at addition level 80 kg P ha-1 of PAPR-40% while copper availability in soil were decreased. Plant height, shoot dry weight and roots dry weight were increased by 6.25%, 28.65% and 99.72% respectively compared with control treatment at level of 80 kg P ha-1. shoot and roots contents of phosphorus and copper concentration were increased at level of 80 kg P ha-1 copper content increased in shoot and roots by 48.81% and 82.10% respectively compared with control treatment.